Post-Soviet Ukraine in the global grain market: supplies for the poor? - D. A. Degterev; K. P. Kurylev (Проблемы постсоветского пространства, 2023)
The authors of the paper examine the problem of the participation of post-Soviet Ukraine in the global grain trade basing on a critical analysis and using extensive statistical data. Grain crops have traditionally occupied the most important place in the agro-industrial complex of Ukraine. Ever since Soviet times, the image of the “all-Union granary” has been entrenched in it, which was especially actively exploited in the last years of the existence of the USSR by nationalist elements, becoming a program for them in the fi ght against Moscow. In fact, the Ukrainian SSR only until the early 1930s was the main base for the production of marketable grain in the USSR. Subsequently, larger grain bases were formed in the RSFSR and KazSSR. After the start of the Special Military Operation, the thesis about Ukrainian grain as a central element of global food security again became a popular narrative and was used against the Russian Federation as part of a global information campaign. This strategic disinformation was intended to infl uence Russia’s actions in the framework of the “grain deal”. The purpose of the study is to fi nd an answer to the question of the extent to which the positions of the Ukrainian side actually correspond to realities. Based on the results of the study, the authors come to the conclusion that the decisive role of Ukraine declared by offi cial Kiev and the West in the supply of grain to global markets is exaggerated. The bulk of the grain is not sent to those countries that are experiencing serious problems with hunger and are vitally dependent on Ukrainian supplies.